Infective endocarditis: the evaluation of 64 cases - Aydın, Selda; Şahin, Meyha; Yılmaz, Ezgi; Mert, Ali (My University, 2024)
Introduction: Infective endocarditis (IE) remains an important infectious disease with a high mortality rate despite advancements in diagnostic and therapeutic methods. Our study aimed to determine the demographic characteristics, clinical, microbiologic, and imaging findings, treatment modalities and clinical outcomes, and factors affecting mortality in IE cases. Materials and Methods: The study was retrospectively designed in a tertiary university hospital. Between January 2015 and December 2023, 64 cases of definite and probable IE in individuals over the age of 18, defined according to the 2023 Duke IE criteria by The International Society for Cardiovascular Infectious Diseases, were included in the study. Results: The median age was 61.5 years (interquartile range= 48-74 years) and 69% (n= 44) were male. The most common symptoms and signs were fever (84.3%), murmur (62.5%), and embolic events (25%). Definite IE was diagnosed in 91% (n= 58) and probable IE in 9% (n= 6) of the patients. Natural valve IE was identified in 51.6% of cases, prosthetic valve IE in 34.4%, and pacemaker IE in 14%. The most commonly affected valves were mitral (35.6%) and aortic (33.3%) valves. Microbiological diagnostic methods identified the causative agent in 89.1% of cases. The most frequently isolated microorganisms were staphylococci (43.8%) and enterococci (21.9%). Surgery was performed in 50% of the patients. The mortality rate during hospitalization was 22%. Higher mortality rates were observed in the presence of advanced age, coronary artery disease, chronic kidney disease, and pacemaker endocarditis. Conclusion: It is noteworthy that the average age of patients with IE is increasing, staphylococci are the predominant microbiological agent, and patients with endocarditis associated with advanced age, chronic kidney disease, and the presence of a pacemaker have a more severe prognosis. These findings emphasize the critical importance of IE management being conducted by an IE team, as recommended in the European Society of Cardiology 2023 endocarditis guidelines.

Giriş: İnfektif endokardit (İE), gelişmiş tanı ve tedavi yöntemlerine karşın günümüzde de yüksek mortalite oranına sahip önemli bir infeksiyon hastalığıdır. Çalışmada İE olgularının demografik özelliklerinin, klinik, mikrobiyolojik ve görüntüleme bulgularının, tedavi yöntemleri ve klinik sonuçlarının, mortalite ile ilişkili durumların belirlenmesi amaçlandı. Materyal ve Metod: Çalışma, üçüncü basamak bir üniversite hastanesinde retrospektif olarak dizayn edildi. Ocak 2015-Aralık 2023 tarihleri arasında izlenen 18 yaş üstü, The International Society for Cardiovascular Infectious Diseases 2023 Duke IE kriterlerine göre kesin ve olası tanı alan 64 İE olgusu çalışmaya alındı. Bulgular: Olguların yaş ortancası 61.5 (çeyrekler arası aralık= 48-74) olup %69 (n= 44)’u erkekti. En sık görülen semptom ve bulgular ateş (%84.3), üfürüm (%62.5) ve embolik olaylar (%25) idi. Hastaların %91 (n= 58)’ine kesin İE, %9 (n= 6)’una olası İE tanısı koyuldu. Hastalarda doğal kapak İE %51.6, yapay kapak İE %34.4 ve pacemaker İE %14 oranında tanımlandı. En sık etkilenen kapaklar mitral (%35.6) ve aort (%33.3) kapaktı. Mikrobiyolojik olarak olguların %89.1’inde etken saptandı. En sık izole edilen mikroorganizmalar stafilokok (%43.8) ve enterokoklardı (%21.9). Hastaların %50’sine cerrahi tedavi uygulandı. Hastane yatışı sırasında gelişen mortalite oranı %22 olarak saptandı. İleri yaş, koroner arter hastalığı, kronik böbrek hastalığı ve pacemaker endokarditinde mortalite oranları daha yüksek gözlendi. Sonuç: Çalışmanın sonuçları İE hastalarında yaş ortalamasının arttığına, stafilokokların baskın mikrobiyolojik etken olarak öne çıktığına, ileri yaş, kronik böbrek hastalığı ve pacemaker zemininde gelişen endokardit hastalığının daha mortal seyrettiğine dikkat çekmektedir. Bu bulgular, İE yönetiminin, European Society of Cardiology 2023 endokardit rehberinde önerildiği gibi IE takımı tarafından yapılmasının son derece önemli olduğunu vurgulamaktadır.
İnfektif endokardit: 64 olgunun değerlendirilmesi
Keywords: Infective Endocarditis; Epidemiology; Mortality; İnfektif Endokardit; Epidemiyoloji; Mortalite